The historical experience of reforms of taxation of individuals in Russia and the Republic of Kazakhstan - Ischuk, T.L.; Baimukhametova, A.S. (KSU Publ., 2020)
Abstract Object:The study evaluates a reasonable logical sequence of actions (stages) from the analysis of the state of the tax system of individuals and making a decision on reform, to the definition of spare options in case of failure. Methods:The theoretical and methodological basis for writing this article are the works of foreign, Russian and Kazakh scientists in the field of theory and methodology of taxation of individuals. Results:The relationship between the measures and results of individual tax reforms based on the experience of Russia, Kazakhstan and other countries from 1991 to 2020 in the framework of ten-year cycles ending in crises, and the provisions of the theories of reforms, taxation, and tax regulation of the economy was revealed. An algorithm for implementing reforms is proposed in (figure 1). Conclusion: The article analyzes the results of reforms of taxation of individuals for the period from 1991 to 2020.On the example of Russia and the Republic of Kazakhstan, taking into account theories of reforms of taxation and tax regulation of the economy.Identified patterns in the periodicity conduct of reforms, good luck and mistakes in their conduct in terms of tax theory, tax regulation of the economy and the theory of reforms. It is proposed to algorithm of carrying of reform of taxation, which can serve as a universal tool for reforming both the entire tax system and its individual elements. The algorithm can serve as a universal tool for reforming both individual subsystems of the state tax system, and for the tax system in general.
Ресей мен Қазақстан Республикасындағы жеке тұлғаларға салық салу реформаларының тарихи тəжірибесі
Исторический опыт реформ налогообложения физических лиц в России и Республике Казахстан
Keywords: taxes; taxation of individuals; personal income tax; income tax; vehicle tax; land tax; property tax of individuals; tax reforms